2011
DOI: 10.1094/phyto-05-10-0133
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora ramorum in Canada: Evidence for Migration Within North America and from Europe

Abstract: Phytophthora ramorum, the cause of sudden oak death on oak and ramorum blight on woody ornamentals, has been reported in ornamental nurseries on the West Coast of North America from British Columbia to California. Long-distance migration of P. ramorum has occurred via the nursery trade, and shipments of host plants are known to have crossed the U.S.-Canadian border. We investigated the genotypic diversity of P. ramorum in Canadian nurseries and compared the Canadian population with U.S. and European nursery is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 28 publications
2
69
0
1
Order By: Relevance
“…For example, ground surveys and geographic information system (GIS) mapping of Dutch elm-diseased and elm bark beetles-attacked trees on the geographically isolated island of Gotland allowed for tracking patterns of disease spread in relation to management strategies to reduce disease prevalence [22]. For many invading forest pathogens, the key to understanding dispersal is by measuring the human transport process through imported plant material via random checks in quarantine facilities from nurseries [23,24], or on vehicles [25]. For example, the spread of P. ramorum has been demonstrated using various approaches such as environmental niche models [26], risk assessment maps based on host distribution [27], landscape structure [28,29], multi-scale patterns of human activity [30], and trade networks [31].…”
Section: Novel Environments Novel Hostsmentioning
confidence: 99%
“…For example, ground surveys and geographic information system (GIS) mapping of Dutch elm-diseased and elm bark beetles-attacked trees on the geographically isolated island of Gotland allowed for tracking patterns of disease spread in relation to management strategies to reduce disease prevalence [22]. For many invading forest pathogens, the key to understanding dispersal is by measuring the human transport process through imported plant material via random checks in quarantine facilities from nurseries [23,24], or on vehicles [25]. For example, the spread of P. ramorum has been demonstrated using various approaches such as environmental niche models [26], risk assessment maps based on host distribution [27], landscape structure [28,29], multi-scale patterns of human activity [30], and trade networks [31].…”
Section: Novel Environments Novel Hostsmentioning
confidence: 99%
“…In addition, the EU1 lineage was frequently detected in Canada. Goss et al (2011) conclude that P. ramorum migration from Europe to North America is more likely to have occurred than migration in both directions. Evidence provided to the Panel by Matteo Garbelotto (University of California, personal communication, 2011), indicates that virulence of isolates belonging to different lineages may differ (Appendix A.…”
Section: General Commentsmentioning
confidence: 83%
“…Additional information Goss et al (2011) studied the genotypes of P. ramorum in plant nurseries in Canada compared to those found in the US and in Europe. The study confirms that plant trade networks have not only made it possible for P. ramorum to be introduced into North America and Europe, but are also likely to introduce new genotypes if left unregulated.…”
Section: General Commentsmentioning
confidence: 99%
“…In the past, many epidemics caused by invasive plants, pathogens, or insects were assumed to be initiated by a single introduction event followed by a radiation from the introduction point. However, several recent studies have found that this is likely not the case and that, in most invasion events, multiple introductions have occurred followed by migration and admixture of populations [58][59][60][61]. This may be particularly true for forest pathogens as damage caused by these organisms may go unnoticed and undetected for decades in more remote areas.…”
Section: Isolates and Genetic Diversitymentioning
confidence: 99%